Wokshop Menggambar Ragam Hias Topeng Kayu Labuapi Menggunakan Totebag di MTs Negeri 1 Mataram - Tesa, Tesa Yustika; Mahroni, Lalu Aswandi; Pamungkas, Bayu Aji; Tomi, Muhammad; Ardi, Raden Fanny Printi (Puslitbang Sekawan Institute Nusa Tenggara, 2024)
Pelaksanaan workshop